2017
DOI: 10.18632/oncotarget.15036
|View full text |Cite
|
Sign up to set email alerts
|

Overwhelming rapid metabolic and structural response to apatinib in radioiodine refractory differentiated thyroid cancer

Abstract: Currently, patients with radioiodine refractory differentiated thyroid cancer (RAIR-DTC) have limited treatment options. In this study, we aimed to assess the short-term efficacy and safety of apatinib in RAIR-DTC. Ten adult patients were prospectively enrolled to receive oral apatinib (750 mg q.d). The primary endpoints were change in serum thyroglobulin (Tg) concentration, disease control rate (DCR) and objective response rate (ORR) based on RECIST 1.1 criteria. The secondary endpoints included change in glu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
44
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(44 citation statements)
references
References 37 publications
0
44
0
Order By: Relevance
“…Apatinib is a novel TKI highly selective for VEGFR2 with good antitumor effects in various types of solid tumors. Apatinib was shown to be safe and highly efficacious in a small number of patients with radioiodine-refractory differentiated thyroid cancer (13). In this report, we investigated the potential therapeutic effect of apatinib on PTC and the mechanism of apatinib in vitro and in vivo.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Apatinib is a novel TKI highly selective for VEGFR2 with good antitumor effects in various types of solid tumors. Apatinib was shown to be safe and highly efficacious in a small number of patients with radioiodine-refractory differentiated thyroid cancer (13). In this report, we investigated the potential therapeutic effect of apatinib on PTC and the mechanism of apatinib in vitro and in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, apatinib has shown antitumor effects in various types of solid tumors in a number of ongoing phase II and III clinical trials (11,12). Lin et al (13) reported that apatinib showed promising efficacy in a small number of patients with radioiodine-refractory differentiated thyroid cancer. However, the antitumor mechanism of apatinib in PTC is unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Apatinib, a highly selective tyrosine kinase inhibitor of VEGFR-2, was proven to have an anti-tumor effect in various tumors 5 7 , 33 . Recently, apatinib has demonstrated a promising therapeutic effect for radioiodine refractory differentiated thyroid cancer 34 , which suggests a novel method for ATC treatment. We previously confirmed that apatinib could significantly reduce ATC angiogenesis in a dose- and time-dependent manner.…”
Section: Discussionmentioning
confidence: 99%
“…The patient in our study has thus far achieved disease-free status for 12 months. Apatinib has produced promising clinical outcomes in several other types of cancer [ 39 43 ], and has a high binding affinity relative to other anti-angiogenic drugs. For example, apatinib ligand-receptor binding is 10 times greater than that of sorafenib [ 44 , 45 ].…”
Section: Discussionmentioning
confidence: 99%